2002
DOI: 10.1063/1.1507829
|View full text |Cite
|
Sign up to set email alerts
|

High-quality SiO2 film formation by highly concentrated ozone gas at below 600 °C

Abstract: Highly concentrated ͑Ͼ93 vol %͒ ozone (O 3) gas was used to oxidize silicon for obtaining high-quality SiO 2 film at low temperature. Compared to O 2 oxidation, more than 500°C lower temperature oxidation ͑i.e., from 830 to 330°C͒ has been enabled for achieving the same SiO 2 growth rate. A 6 nm SiO 2 film, for example, could be grown at 600°C within 3 min at 900 Pa O 3 atmosphere. The temperature dependence of the oxidation rate is relatively low, giving an activation energy for the parabolic rate constant of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 19 publications
3
42
0
Order By: Relevance
“…The value of E a was estimated as 0.35 eV, which is only 1/4 of that for dry O 2 oxidation (1.34 eV) [66], indicating a significant promotion of the oxide growth by atomic oxygen. This value coincides with that for an oxidation process in concentrated (∼97%) O 3 [65]. In addition, a deviation from the Arrhenius dependence below ∼350 • C, which is probably due to a change in the rate-determining process, was also observed for the O 3 oxidation process.…”
Section: Formation Of a Thin Oxide Layer On Siliconsupporting
confidence: 62%
See 1 more Smart Citation
“…The value of E a was estimated as 0.35 eV, which is only 1/4 of that for dry O 2 oxidation (1.34 eV) [66], indicating a significant promotion of the oxide growth by atomic oxygen. This value coincides with that for an oxidation process in concentrated (∼97%) O 3 [65]. In addition, a deviation from the Arrhenius dependence below ∼350 • C, which is probably due to a change in the rate-determining process, was also observed for the O 3 oxidation process.…”
Section: Formation Of a Thin Oxide Layer On Siliconsupporting
confidence: 62%
“…In this subsection, surface oxidation of Si is examined. Low-temperature formation of ultrathin oxide layers on semiconductors [63][64][65] is particularly important in the microelectronics industry for high-density device fabrication on glass or plastic substrates.…”
Section: Formation Of a Thin Oxide Layer On Siliconmentioning
confidence: 99%
“…12 However, Nishiguchi et al applied the Deal-Grove model to ultrathin oxide film and demon-strated that it had validity. 13 Following this precedent, we here attempt to discuss the ozone oxidation characteristics using the Deal-Grove model.…”
Section: Ozone Oxidation Mechanismmentioning
confidence: 99%
“…Therefore, the O( 1 D) process can reduce the thermal budget compared to the conventional oxidation process. We concluded that the only oxidation species in the UV-excited ozone process was O(1D), since atomic oxygen (O( 3 P)) generated by the thermal decomposition of ozone is not easily generated at temperatures lower than 410 C. 6 Finally, we discuss the surface temperature of poly-Si during UV irradiation. We have previously studied the O( 1 D) oxidation of poly-Si substrates.…”
Section: Resultsmentioning
confidence: 99%
“…The ~100% ozone used in these experiments was supplied by a pure ozone generator (Type: MPOGSM1C1; Meidensha Corp., Japan). [2][3][4][5] The use of pure ozone reduces the activation energy for Si oxidation from 0.81 eV for O2 to 0.34 eV, resulting in a reaction temperature as low as 410 C. 6 Below 410 C, the Si oxidation rate decreases abruptly owing to the lack of atomic oxygen in the ground state, O( 3 P), which is produced by the thermal decomposition of ozone. The reactivity of ozone can be further enhanced by photoexcitation using ultraviolet (UV) light, which illuminates the Hartley bands (200 to 300 nm) to produce atomic oxygen in an excited state, O( 1 D).…”
Section: Introductionmentioning
confidence: 99%